(untitled) (Bangladesh Journal of Botany, 2021)
Effects of some environmental variables (moisture, temperature, pH) on the carbon stock and respiration in the rhizosphere soil of Sal (Shorea robusta Roxb. ex. Gaertn. f.) of 11 different Sal forest stands situated in Cumilla, Gazipur, Sherpur, Modhupur, Dinajpur and Rangpur of Bangladesh were assessed. Soil samples were collected from two layers (upper layer, 0 - 15 cm and lower layer, 15–30 cm depth). During February 2019, samples were collected from Kotbari and Rajeshpur of Cumilla and during June 2019, samples were collected from the rest of the stands. The values of different variables showed fluctuations, e.g. moisture content (11.87 - 38.78%), pH (4.73 to 6.03), conductivity (63.13 - 248.83 μS/cm), soil organic carbon (135.43 - 1263.53 ton/ha) and respiration (75.95 - 91.8 mg CO2/g soil) respectively. Rates of respiration increased where pH remained 4 to 6 and the temperature 20 to 34ºC. Rate of respiration also increased when the amount of moisture content and carbon stock decreased. This research will help to understand the role of environmental factors on the variability of soil C dynamics in the natural Sal forest areas of Bangladesh. Bangladesh J. Bot. 50(3): 685-693, 2021 (September)